(untitled) (Journal of Gemilang, 2025)
This study aims to analyze the role of cooperative play in developing social and emotional skills among preschool children using a quantitative approach based on Structural Equation Modeling–Partial Least Squares (SEM–PLS). The sample consisted of 150 preschool children participating in play-based learning activities. The results indicate that cooperative play has a significant positive effect on social skills and directly enhances children’s emotional skills. Furthermore, social skills significantly influence emotional skills and mediate the relationship between cooperative play and emotional development. The model shows an R-square value of 0.532 for social skills and 0.614 for emotional skills. These findings highlight cooperative play as an effective pedagogical strategy for strengthening children’s social-emotional development. This study offers practical implications for educators in designing play activities that emphasize positive interaction and collaboration.